Tire dimensionless numbers for analysis of tire characteristics and intelligent tire signals. (December 2021) - Jeong, Dasol; Choi, Seibum B.; Lee, Jonghyup; Kim, Mintae; Lee, Hojong
Highlights: Proposal for tire model dimensionless numbers through flexible ring tire model. Analysis of tire vibration characteristics through intelligent tires using FFT (fast Fourier transform). Estimation of tire model dimensionless numbers through intelligent tire sensors. Analysis of tire characteristics through tire model dimensionless numbers. Abstract: It is essential to understand and analyze the characteristics of the tire. This paper focuses on analyzing tire characteristics using intelligent tires based on physical tire models. The flexible ring tire model has been selected as the tire model. The flexible ring tire model is analyzed and simplified based on modal analysis. Four tire dimensionless numbers have been proposed to represent tire characteristics using the Buckingham theorem. Tire dimensionless numbers were estimated using intelligent tire sensor signals. The estimation algorithm was designed based on the standing wave characteristics of the tire. The proposed estimation algorithm has been validated through experiments on various tire conditions. The physical correlation between the estimated tire dimensionless numbers and the tire state dimensionless numbers were analyzed. The experimental results verify the physical meaning and estimation performance of the proposed tire dimensionless numbers.